Evaluation of antioxidant properties and nutritional composition of purslane (Portulaca oleracea) from arid regions - K. Makangali; T. Tultabayeva; G. Tokysheva; A. Shoman; V. Kiyan; S. Abzhanova; D. Aiken; D. Amirkhanova; G. Zamaratskaia (Brazilian Journal of Biology)
Abstract This study evaluates the antioxidant properties and nutritional composition of purslane (Portulaca oleracea) grown in the arid region of Kyzylorda, Republic of Kazakhstan. The antioxidant capacity of purslane was assessed using the Ferric Reducing Antioxidant Power (FRAP) assay, yielding values of 43.5 ± 1.0 mg GAE g-1 dry weight, and DPPH radical scavenging activity, with a value of 83.8% at a concentration of 200 mcg/ml. Total phenolic content (TPC) and total flavonoid content (TFC) were recorded at 16.9 ± 0.4 mg GAE g-1 and 26.3 ± 1.0 mg rutin g-1, respectively. Additionally, purslane showed a high omega-3 fatty acid content, with linolenic acid (C18:3) being 26.7 ± 2.1%. The plant is also abundant in essential vitamins and minerals, including vitamin C (20.1 ± 4.6 mg 100 g-1), calcium (7656.2 ± 2663.7 mg 100 g-1), and iron (5309.7 ± 1056.8 mg 100 g-1). These findings support the potential use of purslane as a natural antioxidant source in the food industry and suggest further research into its applications in functional food development.